From Deliberation to Headlines: Media Coverage and Framing of the 2022 Luxembourg Climate Citizens’ Assembly (Klima-Biergerrot) - Paulis, Emilien; Verhasselt, Lisa; Kies, Raphaël (Politics of the Low Countries, 2025)
Climate Citizens’ Assemblies (CCAs) have become a valuable tool for directly involving citizens in addressing the pressing challenges posed by the climate crisis. Central to their legitimacy is their capacity to engage a broad audience with the complexities of participatory and environmental politics. In this respect, the media plays a crucial role in influencing whether and how CCAs are portrayed. Recognizing a lack of research connecting media and (C)CAs, this study aims to advance the research agenda through a case study of the Luxembourgish Klima Biergerrot (KBR). Analysing 120 media pieces, we aim to better understand which factors influence both the volume and framing of a CCA in media discourse. Our findings are three-fold. First, coverage tends to be more extensive and positive when the media focuses on the CCA’s outcomes rather than procedural aspects. Second, media outlets with left-leaning ideologies tend to provide more extensive coverage but frame the CCA more negatively compared to right-leaning counterparts. Third, while the gender of journalists does not affect the extent of the coverage, it influences the framing: women journalists tend to present CCAs more positively. This research underscores the role of the media in communicating CCAs and climate action.